PERAN GERAKAN LITERASI DAN MINAT BACA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - ANIK ZUROIDAH (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
Literacy culture is no longer foreign. Especially in the world of education. But not many know what activities are included in it. An online information states that literacy culture is intended to carry out habits of mind which are followed by reading and writing processes, which in the end can create a work. In Islam, the foundation for literacy activities is very strong. This can be seen in the Al-Alaq verse 1 of the Qur'an, which means: "Read with (mentioning) the name of your Lord who created. From this understanding, to gain skills in life requires the ability to process the knowledge he has acquired. This can be proven by the activities of students who have carried out the stages of the literacy movement starting from the stages of habituation, development and learning. Initially, students' interest in reading at MTsN 5 Jombang was low. With various efforts, gradually the students' interest in reading began to grow. The religious character of MTsN 5 Jombang students varies greatly. This relates to the diverse backgrounds of students. The role of the literacy movement and interest in reading is very important in shaping the religious character of MTsN 5 Jombang students. The visible change in religious behavior is positive behavior in relation to God, others, and the natural surroundings. This is the case with the role of students' reading interest. Interest in reading that grows from literacy movement activities allows students to absorb information from reading material that is read and then make it as a student who has a religious character. ABSTRAKBudaya literasi sudah tidak asing lagi. Apalagi dalam dunia pendidikan. Namun belum banyak yang mengetahui kegiatan apa yang termasuk di dalamnya. Sebuah informasi online menyebutkan bahwa budaya literasi dimaksudkan untuk melakukan kebiasaan berpikir yang diikuti proses membaca dan menulis, yang pada akhirnya bisa menciptakan sebuah karya. Dalam agama Islam, landasan kegiatan literasi ini sangat kuat. Hal ini bisa dilihat dalam Alquran surat Al Alaq ayat 1, yang artinya: “Bacalah dengan (menyebut) nama Tuhanmu yang menciptakan.Dari pengertian ini untuk meraih kecakapan dalam hidup diperlukan kemampuan dalam mengolah pengetahuan yang diperolehnya. Hal ini bisa dibuktikan dengan aktivitas para siswa yang sudah melakukan tahap-tahap gerakan literasi mulai dari tahap pembiasaan, pengembangan, dan pembelajaran. Minat baca siswa MTsN 5 Jombang awalnya rendah. Dengan berbagai upaya lambat laun minat baca para siswa mulai tumbuh. Karakter religius siswa MTsN 5 Jombang sangat bervariasi. Hal ini berkaitan dengan latar belakang siswa yang beraneka ragam.. Peran gerakan literasi dan minat baca sangat penting dalam membentuk karakter religius siswa MTsN 5 Jombang. Adapun perubahan perilaku religius yang tampak ialah perilaku positif dalam hubungannnya dengan Tuhan, sesama, dan alam sekitar. Hal Demikian halnya dengan peran minat baca siswa. Minat baca yang tumbuh dari aktivitas gerakan literasi memungkinkan para siswa menyerap informasi dari bahan bacaan yang dibaca lalu menjadikannya sebagai siswa yang memiliki karakter religius.